A memória no filme Órfãos do Eldorado: uma construção através dos personagens e dos espaços - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
This study proposes an analysis of the film Orphans of Eldorado, by Guilherme Coelho, released in the cinema in 2015. The purpose is to present how a story was retold, which from the memory, characters and spaces are constituted visually and sonorously. The main character is entangled by the Amazonian culture from the moment he hears the legends from the voice of an Florita. From this moment, the film builds the area that links Arminto: river, characters, stories, forest and its memory, this, a space in which the reality and the imaginary of the legends are mixed. Firstly, it was tried to demonstrate the choice accepted by Coelho in his process of creation the film. Following, it is introduced the theoretical concept that will serve as the basis for the analysis of the construction of the film work. To do so, it was used concepts of the memory theory of Jacques Le Goff (1990), Maurice Halbwachs (1990), Michael Pollak (1992), in particular the notions of individual memory and collective memory. In order to create the enchantment of the Amazonian culture, we assume that Coelho used the emblematic images - rivers and forests - to symbolize the imaginary, the impossible, the subjective, characteristics of the Amazon legends. Therefore, we will also base on the discourse of João de Jesus Paes Loureiro (2007) about Amazon, in an attempt to dialogue the cinematographic language with the Amazonian language. The movie Orphans of Eldorado brings us an Amazon still enigmatic and enchanted. Moreover, this is due, in part, to the work done with the images and sonority that give the narrative an enigmatic atmosphere. We classify the production of Guilherme Coelho as a suggestive Cinema, as it provides the spectator with an emotional and poetic catharsis in communion with the Amazonian context.
Keywords: Órfãos do Eldorado - Filme; Cultura Amazônica; CIÊNCIAS HUMANAS